Print-and-Peel Fabrication for Microfluidics: What’s in it for Biomedical Applications? - Thomas, Marlon S. (Springer US, 2009)
This article reviews the development and the advances of print-and-peel (PAP) microfabrication. PAP techniques provide means for facile and expedient prototyping of microfluidic devices. Therefore, PAP has the potential for broadening the microfluidics technology by bringing it to researchers who lack regular or any accesses to specialized fabrication facilities and equipment. Microfluidics have, indeed, proven to be an indispensable toolkit for biological and biomedical research and development. Through accessibility to such methodologies for relatively fast and easy prototyping, PAP has the potential to considerably accelerate the impacts of microfluidics on the biological sciences and engineering. In summary, PAP encompasses: (1) direct printing of the masters for casting polymer device components; and (2) adding three-dimensional elements onto the masters for single-molding-step formation of channels and cavities within the bulk of the polymer slabs. Comparative discussions of the different PAP techniques, along with the current challenges and approaches for addressing them, outline the perspectives for PAP and how it can be readily adopted by a broad range of scientists and engineers.